가공식품 중 메밀 검출을 위한 경합 ELISA의 개발 - 백수연(Su-Yeon Back); 도정룡(Jeong-Ryong Do); 손동화(Dong-Hwa Shon) (한국식품과학회지, 2014)
We developed a competitive indirect enzyme-linked immunosorbent assay (ciELISA) for determining the buckwheat content in processed foods by using rabbit polyclonal antibodies against buckwheat proteins (BWP). The detection limit of this assay was $0.05-100μg/mL$. The cross-reactivities of the anti-BWP antibodies toward BWP, buckwheat flour, whole buckwheat, and cereals (wheat flour, whole wheat, black bean, mung bean, red bean, brack rice, brown rice, glutinous rice, white rice, millet, African millet, nonglutinous millet, adlay, and rye) were 100, 17.9, 11.8, and 0%, respectively. Thus, the antibodies were found to be specific for buckwheat only. When buckwheat flour was heated for 30 min, the mean assay recoveries of BWP were 83.0% at $60-90^{°}C$ and 44.5% at $100^{°}C$. The spike test showed that the mean assay recoveries of buckwheat from raw noodle, boiled noodle, starch gel, and cereal flour were 99.1, 98.6, 81.1, and 104%, respectively. For the 22 commercial items tested, the qualitative coincidence ratio of assay result and the corresponding value indicated on the item's package label was 100%. However, the average quantitative coincidence ratios from 12 commercial items were 31.6%. Thus, the results suggest that ciELISA is an efficient tool to detect buckwheat in processed foods. 메밀로부터 분리한 메밀단백질(BWP)을 토끼에게 면역하여 생산한 특이항체를 이용하여 가공식품 중 메밀의 검출을 위한 간접경합 효소면역측정법(ciELISA)을 확립하였다. 이때, BWP의 검출범위는 $0.05-100μg/mL$이었다. 특이항체 교차반응 결과, BWP, 메밀가루, 통메밀에 대한 반응성은 각각 100, 17.9, 11.8%를 나타내었으며 그 외 곡물 14종에 대한 반응성은 거의 나타나지 않아 메밀에 대한 특이성이 매우 높았다. 메밀가루는 $60-90^{°}C$에서 반응성이 평균 83.0%를 나타내었으며 $100^{°}C$에서는 44.5%로 반응성이 감소하였다. 메밀가루에 대한 spike test에서 메밀 생면, 삶은 면, 묵, 메밀곡물가루에서 평균 분석회수율이 각각 99.1, 98.6, 81.1, 104%로 매우 높게 나타났다. ciELISA에 의하여 22점의 시판시료 중 메밀의 함유량을 조사한 결과, 메밀 함유 표시된 12점에서 평균 분석회수율은 31.6%로 나타났으나 시료 중 메밀의 정성적 검출은 100%로 매우 우수하였다. 본 연구에서 개발한 ciELISA는 가공식품에 함유된 메밀을 검출하는데 매우 효과적으로 활용할 수 있을 것이다.